The relationship between management control systems and corporate financial performance (a moderated regression analysis approach from mining companies in Indonesia) - Anis Rachma Utary (Universitas Hayam Wuruk Perbanas, 2014)
This paper examines relationship between management control system (MCS) and corporate financial performance (CFP). This relationship is moderated by four modera- tor variables business environment, organization structure, business strategy and culture. The data were collected using questionnaires which were distributed to the respondents in accordance with the predetermined data collection procedure. There were 189 questionnaires-distributed to the respondents including 19 regions of min- ing companies in Indonesia. The result indicates that business environment moderates the relationship between MCS and CFP. Organization Structure cannot moderate the relationships between MCS and CFP. Business strategy moderates relationship be- tween MCS and CFP. Culture cannot moderate the relationship between MCS and CFP.